Evaluation of the apical caliber and conicity of medium accessory gutta-percha cones of three Brazilian commercial brands (Research, Society and Development, 2022)
Gutta-percha is considered the best material for filling the root canal and compliance with international standards for its manufacture is extremely important for the filling stage. This research aimed to evaluate the tip diameter and taper of non-standard M-size gutta-percha accessory cones from three different Brazilian brands: Tanari, Odous and MK Life. For this purpose, 20 cones of each brand were photographed, with the aid of a mini microscope with a digital camera attached, to obtain measurements of the following parameters: diameter of the tip (D0), diameter at 3 mm from the tip (D3), diameter at 16 mm of the tip (D16) and taper (C). The measurements found were subjected to statistical analysis and comparisons between groups of means for each evaluated parameter. ANSI/ADA specifications numbers 57 and 78 were used as references for the analysis of the standardization of the tested cones. The respective mean values of D0 and conicity found were 0.05 mm and 0.07 for the Odous cones, 0.15 mm and 0.05 mm for the Tanari cones, and 0.07 mm and 0.05 mm for the MK Life brand icons. With the results in hand, it was possible to conclude that there is no standardization of obturator cones M among the evaluated brands that disagree with the recommended by the ANSI/ADA specifications.